Bioactive potential of Colombian feijoa in physiological ripening stage - Andrea Milena Sánchez-Riaño; José Fernando Solanilla-Duque; Jonh Jairo Méndez-Arteaga; Henry Alexander Váquiro-Herrera (Journal of the Saudi Society of Agricultural Sciences, 2020)
The present study provides the information on the bioactive potential of feijoa (Acca sellowiana (O. Berg) Burret) grown in Colombia, and its byproducts at physiological ripening stage. The antioxidant capacity of the flesh (F), flesh-seed (FS), and peel (P) of feijoa was estimated with ABTS, DPPH, superoxide anion (O2·−) and hydrogen peroxide assays, while the antifungal activities of acetonic-aqueous extracts were determined against Botrytis cinerea and Rhizopus oryzae. In addition, the vegetal extracts were subjected to a phytochemical screening. The results of these tests revealed the presence of phenolic, terpene, and steroidal compounds and vitamins in the three fractions of the fruit. These compounds were responsible for the high antioxidant and antifungal capacities mainly detected in P fraction, followed by FS fraction. The concentration of bioactive compounds and the antioxidant and antifungal effects were observed in the order of P > FS > F. Together these results show that Colombian feijoa in physiological ripening stage may serve as a promising source of bioactive compounds and exhibit various agroindustrial applications.